The Impact of Islamicity Performance Index on the Profitability of Sharia Banks in Indonesia - Fawwa Alamah, Atikah; Nadhirah, Yuha; Putra, Purnama (SAN Scientific, 2025)
This study evaluates the business and social performance of Indonesian Islamic Banking using the Islamicity Performance Index from 2020 to 2022. Business performance is measured through the Profit Sharing Ratio (PSR) and Islamic Income vs. Non-Islamic Income Ratio (IIR), while social performance is assessed using the Zakat Performance Ratio (ZPR) and Equitable Distribution Ratio (EDR). A purposive sampling method was employed, selecting 12 Indonesian Islamic banks, with data sourced from their Annual Reports. The research applies a quantitative methodology, analyzing data through multiple linear regression using SPSS 22. The study identifies Zakat Performance Ratio (ZPR) as the sole variable positively affecting profitability (ROA), while PSR, IIR, and EDR have no significant impact. The findings underscore the importance of integrating Sharia principles into operational practices. The managerial implications suggest that Sharia bank management should focus on improving ZPR by emphasizing equitable wealth distribution and adherence to Islamic values to enhance profitability. This study provides valuable insights for the Islamic banking sector, emphasizing the need for a holistic approach that aligns with the Islamicity Performance Index to achieve both financial and social objectives.